2015
DOI: 10.1097/md.0000000000001005
|View full text |Cite
|
Sign up to set email alerts
|

Techniques of Fluorescence Cholangiography During Laparoscopic Cholecystectomy for Better Delineation of the Bile Duct Anatomy

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 29 publications
2
84
0
1
Order By: Relevance
“…The majority of previous investigations were small, prospective non‐controlled and controlled studies, and these indicated that the ability of fluorescence cholangiography to visualize the critical junction was equal to that of X‐ray cholangiography. A recent RCT including 639 patients compared fluorescence cholangiography with white light (normal vision) and not with X‐ray cholangiography as the standard.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of previous investigations were small, prospective non‐controlled and controlled studies, and these indicated that the ability of fluorescence cholangiography to visualize the critical junction was equal to that of X‐ray cholangiography. A recent RCT including 639 patients compared fluorescence cholangiography with white light (normal vision) and not with X‐ray cholangiography as the standard.…”
Section: Discussionmentioning
confidence: 99%
“…Misidentification, with a reported incidence ranging from 0.08% to 1.5%, is accomplished with a morbidity up to 21% and high healthcare costs . The use of intravenously ICG injection for identification of the bile ducts with NIR fluorescence cholangiography was evaluated in 30 studies, which showed a pooled cystic duct identification in 1019/1050 (97%) patients . Although, the biliary ducts could be very well visualized, the diminished visualization of the bile ducts in minority of the patients, could be caused by inflammatory tissue or fatty peritoneum (in obese patients) covering the biliary ducts, which hampered the penetration of NIR light .…”
Section: Visualization Of Vital Structuresmentioning
confidence: 99%
“…It is possible that the laparoscope was at different distances from the ureter, resulting in different amounts of fluorescence being detected and influencing the TBR. Kono and colleagues19 reported that the signal contrast on fluorescence images of bile duct samples differed significantly between the laparoscopic imaging systems, and tended to decrease as the laparoscope–target distance increased and porcine tissues covering the samples became thicker.…”
Section: Discussionmentioning
confidence: 99%